Adolescent Pregnancy And Low Birth Weight - Saxena, Vartika (Indian Journal of Community Health, 2004)
Research Question : Is there any difference between educational status, Parity & obstetrical risk status between adolescent & adult pregnant women? Is there any difference in the incidence of Low Birth weight between adolescent and adult pregnant women? Objectives : To compare the pregnancy outcome of adolescent mothers with the adult pregnant women. Study Design : Longitudinal descriptive study. Setting : Sarojini Nagar Block of Lucknow District, Uttar Pradesh Study Variable : Educational status, Parity. Obstetrical risk status. Low Birth Weight. Statistical Analysis : Percentages & Chi2 Square Test Results : The incidence of abortion (8.7%), still birth (6.2%) was higher in adolescent (<18yrs.) compared to adult pregnant women (>1 Byres.) with abortion noted to be 3.8% and stillbirths only 3.1%. Adolescent pregnancy resulted in 5 times higher incidence of birth of low birth weight baby (<2.5kg)- incidence of LBW being 48.7% among adolescent mothers as compared to only 9.8% in adult pregnant women. Conclusion : Adolescent pregnancies not only terminate into higher incidence of abortion and still births but is a major contributory cause of high incidence of low birth weight.